If f(x) = 3^x + 10x and g(x) = 4x – 2, find (f + g)(x).

A. 3^x + 6x + 2
B. 3^x + 14x – 2
C. 3^x – 6x + 2
D. 17x - 2

Respuesta :

Answer:

  B.  3^x +14x -2

Step-by-step explanation:

In general, the expression (f ⊛ g)(x) will mean the operation ⊛ will be performed on the values of the functions:

  (f ⊛ g)(x) ≡ f(x) ⊛ g(x)

The exception is the "ring" or "composition" operator, which indicates the left function is performed on the right function:

  (f ∘ g)(x) ≡ f(g(x))

The expression (f +g)(x) means the function values are added.

__

function sum

For the functions here, we add them by combining like terms:

  (f +g)(x) = f(x) +g(x)

  = (3^x +10x) +(4x -2)

  = 3^x +(10 +4)x - 2

  = 3^x +14x -2 . . . . . . . . . corresponds to choice B

Answer:

The correct option is B. [tex](f+g)(x)=3^{x}+14x-2[/tex]

Step-by-step explanation:

Consider the provided function:

[tex]f(x)=3^{x}+10x[/tex] and [tex]g(x)=4x-2[/tex]

[tex](f+g)(x)[/tex] is saying we want to add [tex]f(x)[/tex]and [tex]g(x)[/tex].

In order to find the value of [tex](f+g)(x)[/tex] simply add them as shown below:

[tex](f+g)(x)=3^{x}+10x+4x-2[/tex]

[tex](f+g)(x)=3^{x}+14x-2[/tex]

Therefore, the correct option is B. [tex](f+g)(x)=3^{x}+14x-2[/tex]